9514 1404 393
Answer:
G 45
Step-by-step explanation:
If Z is the circumcenter, it is equidistant from the vertices T, U, V. That is, ΔZUV is an isosceles triangle and Y is the midpoint of UV.
If Y is the midpoint of UV, then UY = VY = 22.5, and UV = UY +VY = 45.
The length of UV is 45.
Answer:
<em>g(</em><em>x)</em><em> </em><em>=</em><em> </em><em>-4g(</em><em>x)</em><em> </em><em>=</em><em> </em><em>-x+</em><em>4</em>
<em>=</em><em> </em><em>g(</em><em>5</em><em>)</em><em> </em><em>=</em><em> </em><em>-</em><em>4</em><em>(</em><em>5</em><em>)</em><em> </em><em>=</em><em> </em><em>-</em><em>(</em><em>5</em><em>)</em><em>+</em><em>4</em>
<em>=</em><em> </em><em>g(</em><em>5</em><em>)</em><em> </em><em>=</em><em> </em><em>-</em><em>2</em><em>0</em><em> </em><em>=</em><em> </em><em>-</em><em>1</em>
Volume of a cylinder = base x height
the base is the area of the circle at the bottom.
To find the area of a circle, you use:
A = πr²
where r is the radius of the circle.
radius is half of the diameter, so with a diameter of 12.3, (divide that by 2) the radius of the circle is 6.15 feet.
A = π(6.15)²
A ≈ 118.82
Since we know the height is 25 feet, we can solve for the area of the cylinder.
Area of the cylinder = 118.82 x 25 = 2,970.57 feet cubed
Answer:
<u>Linear relationship</u>: increasing or decreasing one variable will cause a corresponding increase or decrease in the other variable.
<u>Inverse relationship</u>: the value of one variable decreases as the value of the other variable increases.
<u>Exponential relationship</u>: a constant change in the independent variable (x) gives the same proportional change in the dependent variable (y)
<u>Question 5</u>
As the x-value increases (by one unit), the y-value decreases.
Therefore, this is an inverse relationship.
The y-values are calculated by dividing 35 by the x-value.
**I believe there is a typing error in the table and that the y-value of x = 3 should be 11.67**
<u>Question 6</u>
As the x-value increases, the y-value increases. The y-value increases by a factor of 5 for each x-value increase of 1 unit.
Therefore, this is an exponential relationship.
<span>6 - 3(4 - 3x)
= 6 - 12 + 9x
= 9x - 6
hope it helps</span>